Effect of spraying Salicylic acid and foliar Nutrients on Vegetative Characteristics of Ber (Ziziphus mauritiana Lamk.) Transplants cv.Tuffahy - Jumaa, Farouk Faraj; zainaldeen, Mohamed Ali (Journal of Kerbala for Agricultural Sciences, 2014)
This study was conducted at pomology orchard of the Department of Horticulture, college of Agriculture, University of Baghdad, during growing seasons of ع0is study was conducted in pomology orchard, Department , College of Agriculture , University of Bagdad, during saeasons 2012 and 2013, to examine the effect of foliar spray of Salicylic acid, Foliartal nutrient and humic acid on the growth of ber transplants C.V Tuffahy. Salicylic acid was sprayed at (0 , 50 , 100 and 200 mg.L-1) while Foliartal and Humic acid were sprayed at (2.5 , 5 ml.L-1) and (0.75 , 1.5 ml.L-1)respectively. A factorial experiment in (R.C.B.D)with three replications was adopted. Results could be summarized as follows at : Foliar spray with Salicylic acid especially 200 mg.L-1 showed significantly increased growth traits with (67.87 , 124.03 %) , (80.70 , 102.38 %) , (59.44 , 71.11%) , (13.24 ,3.95%) , (22.01 , 29.10%) for the characters : plant high, Leaves area , chlorophyll , leaf dry matter and branches contect of carbohydrate for both seasons respectivety Foliar spray of Humin acid at 1.5 mg.L-1 caused significantly in creased in plant high , leaves area , chlorophyll and the percentage of dry mater and carbohydrate with percents reached (52.09,68.36%), (84.71,107.35 %) , (49.17 , 52.73 %) , (9.67 , 5.88 %) , (15.94 , 17.19 %) for both seasons respectively. Foliartal nutrient at 5ml.L-1 concentration significantly increased all vegetative characters at different perecents which varied between the lowest level of (9.22 , 3.12%) for dry matter and the highest leval of (50.23 , 50.18 %) for plant high. The interaction between salicylic acid at 200 mg.L-1 and humic acid at 1.5 ml.L-1 gave the highest values for most vegetative characteristics.